Feminisme dan Ekofeminisme dalam persfektif critical theory - Aziz, Abdul (PSW, 2011)
Abstract: the logical consequences of the differences between men and women in biology and psychologyÂ point of view are seen in the lame of interaction of both in social context. The implication of all that ultimately determine the distinction of roles which was rooted in value systems, beliefs, political, social and economic. During the different roles that occurs while providing opportunities for both sexes to choose, the gender does not matter. However, if the roles are then to compartmentalize the options such that either of the sexes loses the right to vote, then this is where there are problems of gender. Related to this, the review of academic studies in a variety of perspectives on gender, feminist theory that many variations, has caused various reactions from all experts both from in the scientists, observers of women, activists and others who gathered in the one hole that does not end melee concept. But the way this feminist theory also get update as well as criticism from feminist themselves, such as the restoration of ecofeminism theory that attempt the feminist identity back into the nature.